A ação pastoral de Padre Cícero a partir dos sertanejos: fé compromisso e libertação - Abruzio, Ulisses (2008)
The present study analyses the trajectory and the pastoral action of Priest Cícero in the city of Juazeiro do Norte. Facing the perspective of the evangelization, Priest Cícero was the messenger of the freedom of the oppressed people, constantly spoiled and explored by a political system and a dominant class. The context of the end of the XIX century reveals the dichotomy between the religiosity of the official Church and the popular religion. Against this reality, Priest Cícero rises with your pastoral action in search of the freedom of the simple people, respecting your traditions and your religiosity, committing himself with the transformations through the faith. Associating faith and life and putting the people as active agent of your own history, it s not an overplay to say that Priest Cícero created, although in a embrionary way a proto-theology, later called as Theology of Freedom